2023
DOI: 10.3390/su15043103
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies of the Corrosion Inhibition Performance of a Quaternary Phosphonium-Based Ionic Liquid for Mild Steel in HCl Medium

Abstract: The corrosion inhibition performance of a quaternary phosphonium-based ionic liquid, i.e., hexadecyltriphenylphosphonium bromide (HPP), on mild steel in 1 M HCl solution was investigated by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) methods. The surface characterization of mild steel was examined by scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS). The results revealed that the inhibition efficiency increases with its increasing concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Nanoparticles have unique properties, such as high surface area-to-volume ratio, and can significantly improve the corrosion resistance of metals. For example, researchers have shown that the use of nano-TiO2 can reduce the corrosion rate of mild steel in acidic solutions [66]. Additionally, the use of graphene oxide (GO) as a corrosion inhibitor has also been investigated, and it has been shown to improve the corrosion resistance of metals.…”
Section: Recent Advances and Future Directionsmentioning
confidence: 99%
“…Nanoparticles have unique properties, such as high surface area-to-volume ratio, and can significantly improve the corrosion resistance of metals. For example, researchers have shown that the use of nano-TiO2 can reduce the corrosion rate of mild steel in acidic solutions [66]. Additionally, the use of graphene oxide (GO) as a corrosion inhibitor has also been investigated, and it has been shown to improve the corrosion resistance of metals.…”
Section: Recent Advances and Future Directionsmentioning
confidence: 99%